Facility layout design with ARC and ARD methods to minimize transportation time at PT. XYZ - Priyo Yudo Abadi; Eko Poerwanto; Marni Astuti; Riani Nurdin; Gunawan Gunawan; Yasrin Zabidi (Institut Teknologi Dirgantara Adisutjipto, 2026)
Every manufacturing company such as PT. XYZ always wants effective and efficient production activities, poor facility layout can result in several problems that can later disrupt production activities in manufacturing companies. This study aims to redesign the layout of production facilities and minimize transportation time and identify the causes of production obstacles. The existing layout is analyzed using the Activity Relationship Chart (ARC) and Activity Relationship Diagram (ARD) methods to determine the level of importance between work stations followed by calculating the standard time of each Bomb P-500 Practice production process to determine the transportationtimeintheprocesswithresearchvalidationusing flexsimsimulation.TheresultsoftheActivityRelationshipChart (ARC) and Activity Relationship Diagram (ARD) analysis produced a proposed layout with a more effective and efficient travel distance and transportation time when compared to the initial layout with a comparison that the travel distance of the proposedlayoutis53.2%shorterwithadistancereductionof191 metersandthetotaltransportationtimeoftheproposedlayoutis 53.4% faster with a transportation time reduction of 28.01 minutes while in the simulation conducted the travel distance of theproposedlayoutis32.3%shorterwitha distancereductionof 82.03meters.